2017
DOI: 10.1016/j.cmet.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

SREBP1 Contributes to Resolution of Pro-inflammatory TLR4 Signaling by Reprogramming Fatty Acid Metabolism

Abstract: Macrophages play pivotal roles in both the induction and resolution phases of inflammatory processes. Macrophages have been shown to synthesize anti-inflammatory fatty acids in an LXR-dependent manner, but whether the production of these species contributes to the resolution phase of inflammatory responses has not been established. Here, we identify a biphasic program of gene expression that drives production of anti-inflammatory fatty acids 12–24h following TLR4 activation and contributes to down-regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
231
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(252 citation statements)
references
References 46 publications
17
231
0
4
Order By: Relevance
“…Furthermore, Li et al [41] suggest up-regulation of LXR-regulated genes encoding enzymes involved in the synthesis of long chain PUFAs with known antiinflammatory activity including palmitoleic acid, eicospentaenoic acid (EPA), and docosahexaenoic acid (DHA) is essential for the anti-inflammatory phenotype observed in Ncor1 knockout mice. The observation that treatment of macrophages with LPS in vitro transiently inhibits fatty acid synthesis [5] further supports the hypothesis that fatty acids may play important roles in limiting inflammation. The re-establishment of fatty acid synthesis observed at later stages after LPS administration has been proposed to play a role in the subsequent resolution of the inflammatory response [5].…”
Section: Linking Lipid Metabolism and Inflammationsupporting
confidence: 63%
See 1 more Smart Citation
“…Furthermore, Li et al [41] suggest up-regulation of LXR-regulated genes encoding enzymes involved in the synthesis of long chain PUFAs with known antiinflammatory activity including palmitoleic acid, eicospentaenoic acid (EPA), and docosahexaenoic acid (DHA) is essential for the anti-inflammatory phenotype observed in Ncor1 knockout mice. The observation that treatment of macrophages with LPS in vitro transiently inhibits fatty acid synthesis [5] further supports the hypothesis that fatty acids may play important roles in limiting inflammation. The re-establishment of fatty acid synthesis observed at later stages after LPS administration has been proposed to play a role in the subsequent resolution of the inflammatory response [5].…”
Section: Linking Lipid Metabolism and Inflammationsupporting
confidence: 63%
“…Initial studies using electrophoretic shift mobility assays and promoter analyses identified direct repeats of the classic nuclear receptor‐binding motif AGGTCA separated by four nucleotides (DR4) or inverted repeats of the same sequence separated by 1 nucleotide (IR1) as high‐affinity binding sites for LXR‐RXR heterodimers . These sequence preferences have largely been confirmed by genome‐wide chromatin immunoprecipitation sequence experiments .…”
Section: Dna Binding and Transcriptional Controlmentioning
confidence: 96%
“…Weak interactions were also detected between F12-like and NF-KB p65 and RNA Pol II in thioglycolate-elicited MFs [191]. …”
Section: Resultsmentioning
confidence: 99%
“…SREBP1 expression is induced in MΦs upon inflammatory stimulation, which both promotes acute inflammatory responses (Im et al, 2011; Reboldi et al, 2014) and contributes to the resolution of the pro-inflammatory TLR4 signaling(Oishi et al, 2017). However, the reduction of CYP51A1 expression in response to LPS was observed in the absence of SREBP processing or SREBP2 expression, indicating that additional mechanisms must account for the early decreased expression of Cyp51A1 observed upon inflammatory stimulation.…”
Section: Discussionmentioning
confidence: 99%